Sanctioning and Trustworthiness Across Ethnic Groups: Experimental Evidence from Afghanistan - Ian Levely; Vojtech Bartos (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2018)
We show how sanctioning is more effective in increasing cooperation between groups than within groups. We study this using a trust game among ethnically diverse subjects in Afghanistan. In the experiment, we manipulate i) sanctioning and ii) ethnic identity. We find that sanctioning increases trustworthiness in cross-ethnic interactions, but not when applied by a co-ethnic. While we find higher in-group trustworthiness in the absence of sanctioning, the availability and use of the sanction closes this gap. This has important implications for understanding the effect of institutions in developing societies where ethnic identity is salient. Our results suggest that formal institutions for enforcing cooperation are more effective when applied between, rather than within, ethnic groups, due to behavioral differences in how individuals respond to sanctions.
Keywords: D01; D02; C93; J41; 330; sanctions; cooperation; crowding out; moral incentives; ethnicity; afghanistan